Evaluation of physical fitness in junior football players - Torres-Luque, G.; Calahorro, F.; Cachón Zagalaz, J.; Lara-Sánchez, A. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Monitoring and assessment of physical fitness is currently employed to determine the physical state of soccer players at certain times during the season and it provides control and possible adaptation´s of planning and training according to the capabilities of players. The footballer, to yield a competitive level requires a combination of qualities. These physical and functional parameters are essential for performance in competition, requiring adequate levels of endurance, strength, flexibility and speed, along with proper coordination, balance, agility and cognitive ability for taking the right decisions during the game (Reilly et al., 2000). In addition, they argue that it would be interesting to control and monitor these variables during the player´s development, as they can determine the future athletic performance at this age of formation. Methods: 29 players were selected to determine their body composition (Inbody 720), maximum strength in bench press, hamstring flexibility (Sit and Reach test), countermovement jump and Abalakov jump (Platform Musclelab 4000), and maximal oxygen consumption (Course Navette test) during 3 days. For statistical analysis SPSS v.15 for Windows was used. Results: The following results were found. The body fat percentage and body muscle percentage were 10,94±3,09% and 31,52±1,55% respectively. There was a maximum volume of oxygen consumption of 61,60±2,51 ml·kg·¬¹min¬¬², a maximal aerobic speed of 14,48±0,41 km/h, a maximum strength bench press of 66,44±9,82 kg, a contermovement jump of 38,08±3,70 cm, an Abalakov jump of 46,22±5,00 cm and a hamstring flexibility of 24,96±7,26 cm. Discussion: The average values of results indicate similar values or slightly lower values compared to elite for body mass index, body fat percentage, maximum volume of oxygen consumption, Abalakov jump and hamstring flexibility. Results are similar in maximal aerobic speed to amateurs and much higher values for maximum strength bench press in amateurs and lower in contermovement jump and body fat percentage (Stroyer et al., 2004; Le Gall et al., 2008). The results show that group values are similar to those found in the literature for junior and young soccer players.